Prevalence of anaemia and its associated factors among the pregnant women receiving antenatal care in a maternity hospital, Bengaluru - Balakrishna, Ananya M.; S. Padmanabha, Usha Rani; Maheswaran, Rajappa (International Journal Of Community Medicine And Public Health, 2019)
Background: Anaemia affects 1.62 billion people globally which corresponds to 24.8% of the population and the prevalence of anaemia in pregnant women is 56 million. In India 16% of maternal deaths are attributed to anaemia with prevalence of 50.3%. Hence, this study was done to assess the prevalence of anemia and its associated factors among the pregnant women attending the maternity hospital. Methods: A hospital based cross section study was done among pregnant women receiving antenatal care over a period of 2 months. Based on the prevalence rate of anaemia; 39.6%, the estimated sample size was 368. Haemoglobin was estimated by cyanmethaemoglobin method. All pregnant women who voluntarily agreed to participate were selected by systematic sampling method. Results: Majority of subjects were in the age group of 15 to 24 years, 60.6%. Nearly 90% were Hindus, 83.2% were homemakers and 62% belonged to nuclear family. The prevalence of anaemia was 56% in which 46.6% had mild anaemia, 51.9% had moderate and 1.5% were severely anaemic. Univariate analysis showed religion, occupation, gestational age and history of abortion being associated with anaemia. In multivariate analysis women in first trimester of pregnancy and history of abortion were significant factors for anaemia. Conclusions: In developing nations like India anaemia is a major public health problem contributing to maternal and infant mortality and morbidities; henceforth there is a need for an effective intervention in the form of health education modules to the community and nutritional counseling for women in the reproductive age group about the importance of Iron supplementation during antenatal period.